Voltammetric determination of heavy metals in honey bee venom using hanging mercury drop electrode and PLA/carbon conductive filament for 3D printer - Choinska, Marta; Hrdlička, Vojtěch; Šestáková, Ivana; Navrátil, Tomáš (Monatshefte fur chemie, 2021)
A new method for determination of selected heavy metals (Cd, Pb, Cu, Zn, and Ni) in honey bee venom was developed. Heavy metals are metabolized and incorporated into bee products, including honey and honey bee venom (apitoxin). Their composition reflects contamination of "bee environment", providing information about heavy metal contamination in the neighborhood of human dwellings. Moreover, assessment of bee products contamination is relevant for medicine, as they are a tool for promising therapeutic and chemoprophylactic strategies against COVID-19 (SARS-CoV-2). Owing to the complicated matrix, the developed method consists of wet mineralization with sulfuric acid, nitric acid, under increased temperature, and pressure and subsequent repeated boiling with concentrated nitric acid. Determination of the selected metals was carried out by anodic or cathodic stripping voltammetry on two types of electrodes: pen-type hanging mercury drop electrode (HMDE) and PLA filament with carbon conductive admixture (PLA-C) for 3D printer. Contents of lead and cadmium in all analyzed bee venom samples were on the level of mg kg-1, of nickel and copper about ten times higher, and of zinc on the level of g kg-1. The results achieved using HMDE were recorded with average relative standard deviation (RSD) 5.4% (from 3.2% to 8.6%) and using PLA-C 11.8% (from 6.5% to 18.0%). The results achieved using both electrodes proved to be equivalent with statistical probability higher than 95%.
Keywords: Heavy metals; PLA filament with carbon conductive admixture (PLA-C) for 3D printer; Honeybee venom; Mineralization; Anodic stripping voltammetry; Pen-type hanging mercury drop electrode